Assessment of Groundwater Resources in Jaffna Limestone Aquifer - M. Thushyanthy; C.S. De Silva (Tropical Agricultural Research, 2015)
This study is centered on quantitative estimation of groundwater resources of a selected study area in a limestone aquifer, which is the main resource for agriculture, domestic use and water supply in Jaffna Peninsula. Inflow to the system includes groundwater recharge from precipitation and irrigation and outflow to the system includes lateral groundwater outflow and groundwater extraction. Results showed that the total average annual withdrawal from the study area (0.66 MCM) exceeded the total average annual recharge (0.57 MCM), implying that the system is in deficiency indicating unsustainable water withdrawal. A further recommendation is the establishment of an institution for a groundwater regulatory frame work to optimize the usage of groundwater and to arrest negative groundwater balance. Tropical Agricultural Research Vol. 23 (2): 177 - 185 (2012)